Farmer perception of fall armyworm (Spodoptera frugiderda J.E. Smith) and farm‐level management practices in Zambia. Issue 10 (8th July 2019) - Kansiime, Monica K; Mugambi, Idah; Rwomushana, Ivan; Nunda, Winnie; Lamontagne‐Godwin, Julien; Rware, Harrison; Phiri, Noah A; Chipabika, Gilson; Ndlovu, Mathias; Day, Roger
Abstract: BACKGROUND: This paper documents farmer perceptions and management practices for fall armyworm ( Spodoptera frugiderda J.E. Smith), providing a baseline for the development of sustainable pest management strategies. RESULTS: 91% of farmers correctly identified fall armyworm, and reported it as the most important maize pest during 2016/2017 cropping season, affecting nearly half of cultivated area. Estimated maize yield loss during the season, attributed to fall armyworm was 28%. A majority of farmers (60%) used pesticides for fall armyworm control, along with other cultural/physical practices – hand picking and crushing egg masses/caterpillars (36%), and application of ash/sand in the funnel (19%). Farmers used various pesticide active ingredients, and protective measures were inadequate; >50% of farmers did not use any protective measures while spraying. Significantly more male than female farmers used pesticides ( P = 0.05), and the reverse was true for cultural practices. Significant maize yield differences ( P = 0.001) were observed by gender, attributed to differences in utilization of production inputs/practices. At least 77% of farmers received and shared agricultural advice, which can be optimized to spread information on fall armyworm management options. CONCLUSION: Increased use of pesticides to manage fall armyworm poses health and environmental risks, besides the high cost for farmers and governments. Research into cultural and indigenous practices used by farmers will offer opportunities for alternative and sustainable management practices. Research efforts should pay attention to gender differences in access to resources and inputs. Tackling fall armyworm at the farm level, and averting yield losses will require integrated messaging addressing other production risks. © 2019 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Effective pest control to a large extent depends on farmers' knowledge and behavior towards pest management. This article presents analysis of farmer perceptions of the invasive fall armyworm in Zambia.